Analisis Strategi Pembelajaran Matematika Pilihan Guru - Putra, Aan; Fadhillah, Ulfa; Anggraini, Reri Seprina (Universitas Negeri Surabaya, 2025)
Basically, there is no strategy that is suitable for all mathematics topics, so variations in mathematics learning strategies are needed. However, teachers often choose learning strategies or methods that are more practical for teachers even though they are not in accordance with the student-centred learning approach. Therefore, this study aims to describe teachers' considerations in choosing mathematics learning strategies and their implementation. This study uses a qualitative descriptive approach involving two mathematics teachers who each teach at one of the state junior high schools (SMP) and one of the state Islamic junior high schools (MTs) in Sungai Penuh, Jambi as research subjects. The researchers conducted observations of the learning implementation, semi-structured interviews with teachers about considerations for choosing learning strategies, and documentation of learning devices. Data were analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The data trustworthiness used the source triangulation method. The results of the study showed that the learning strategy used by teachers was direct instruction with a pattern of teacher explanations, sample questions, and exercises. Direct instruction was chosen for reasons of practicality and the limited choice of other learning strategies mastered by the teacher. The researcher encourages a comprehensive evaluation of the learning implementation by teachers as well as the provision of ongoing training to improve teacher competence.